Take off, plug in, dial up [aicraft personal communication]. - Karlin, S.
The author describes how commercial airlines are now looking to deploy a slew of new in-flight technologies for business as well as entertainment. He explains how e-mail, Web surfing, cell phones and more will be coming to a plane near you
Keywords: Web surfing; Aircraft personal communication; Business; Cell phones; Commercial airlines; E-mail.; Entertainment; In-flight technologies